Pengembangan Buku Pendamping Pembelajaran Menulis dengan Pendekatan Ilmiah Kelas IV Sekolah Dasar - Murwaningsih, Sri Dwi (SCAD Independent, 2025)
This development research aims to improve writing skills Elementary School fourth grade students through the development of a companion book of learning to write with a scientific approach. It also describes the quality of the companion book both in quality products and quality of use in the classroom. Developing the process of developing a companion book of learning to write with a scientific approach using 4-D models adopted from Thiagarajan. The research was conducted in three stages: (1) The definition phase consists of a front and analysis, student analysis, concept analysis, task analysis, and the formulation of objectives; (2) The design phase consists of arranging the reference benchmark, media selection and preliminary design; (3) the development stage in the form of media development phase, which consisted of expert validation and test development. Data results obtained were as follows: the contents of expert validation get a score of 80.63% in feasible criteria. At the trial limited to the activities of teachers got 94.3% with very good criteria, the response of teachers got 75% good criteria, student activity got 71.4% good criteria, the students response got 94.3% very good criteria, experiencing an increase in student learning outcomes 57%. As for the extensive testing the activity of teachers got 94.3% with very good criteria, teachers response got 77.8% good criteria, student activity got 71.4% good criteria, the response of students got 94.6% very good criteria, the results of student learning experience an increase of 32%. Based on the results of data analysis, it can be concluded that the development of a companion book of learning to write with a scientific approach to learning Indonesian can improve students' writing ability.